Quasigraphs in n-Dimensional Manifolds - Casciani, Marino P. (My University, 1976)
A definition of quasigraphs in n-dimensional manifolds in given. A continuous family of quasigraphs is then introduced and the intersection and support properties of these quasigraphs are studied.
Keywords: Mathematics; Mathematics